Medical classification in sport of disabled people - Beniamin Szmelcer; Agata Trzebiatowska; Michał Wilczyński; Paulina Miętkowska; Małgorzata Gajos; Natalia Skierkowska; Monika Prylińska; Jakub Husejko; Oktawia Wysocka; Weronika Topka; Magdalena Łabędź; Kornelia Kędziora-Kornatowska (Journal of Education, Health and Sport, 2018)
Background: In the live of disabled people sport is very important not only in terms of health, but often becomes a passion that gives the life meaning. For many disabled athletes this passion becomes their profession. Medico-sport classification divides athletes into groups and classes based on the type of the physical and mental dysfunction in order to equalize the odds in a sports competition. Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: disabled, sport, classification, dysfunction. Results: Medical-sport classification distinguishes groups of disability of: sight, hearing, limb dismemberment, paraplegia, diseases of the musculoskeletal system, cerebral palsy and intellectual disability. In the professional sport the athletes classification is done by medical doctors in cooperation with physiotherapists under the supervision of the Central Classification Committee of the “Start” organization, which verifies and approves the athletes membership to a certain group or class. During the athletes World Championships decision about the classification is done by the International Paralympic Committee (IPC), Cerebral Palsy International Sports and Recreations Association (CP – ISRA) and International Wheelchair and Amputee Sports Federation (IWAS). The group/class examination is carried out during the most important sports events like Paralympic Games, World Championships and European Athletics Championships, and remains valid for the next four years. Conclusions: The aim of this classification is to make the athlete’s achievement in a sport competition be a result of the athlete’s physical and psychological training rather than the level of his or hers disability. The subject of grouping and classification of the disabled athletes still remains an open topic for discussion.